Faktor Yang Mempengaruhi Produksi Bawang Merah (Allium Ascalonium l) Di Kabupaten Demak - Awami, Shofia Nur; Sa'diyah, Khalimatus; Subekti, Endah (LPPM Universitas Malikussaleh - Indonesia, 2018)
This research aimed to determine the cost of production, revenue and income shallot farm, as well as the factors that influence of shallot production in Gajah Village Gajah District Demak Regency. Sampling technique of respondents was done purposively. Respondents used in this research were 50 respondents. Data analysis methods used in this study are cost analysis, revenue, income and multiple linear regression analysis. Based on the results of data processing for own land obtained an average total cost Rp 27,329,496/planting season or Rp 49,112,867/ha/planting season. The average revenue is Rp 44,253,667/planting season or Rp 86,802,491/ha/planting season. So the average income is Rp 16,924,171/planting season or Rp 37,689,624/ha/planting season. For lease land the average total cost is Rp 36,701,625/planting season or Rp 56,736,125/ha/planting season. Average revenue is Rp 51,154,125/planting season or Rp 81,800.358/ha/planting season. So the average income is Rp 14,452,500/planting season or Rp 25,064,234/ha/planting season. Based on data analysis using multiple linear regression, it is known that the value of determination coefficient (R2) 0.934. The shallot production in Gajah Village Gajah District Demak Regency were influenced by several factors including; the land area, the seed, the fertilizer, the land ownership, and the shallot varieties.